SURFACE FLUX â WIND PROFILE RELATIONSHIP IN CONVECTIVE CONDIT IONS: A NEW RESULT - Santoso, Edi (BPPT, 2001)
A new improved flux â profile relationship for winds in convective conditions isconstructed from convective transport theory and radix layer theory. Data from theMinnesota field experiment are used to recalibrate the new parameterization andsimilarity equation, and data from BLX96 are used to determine whether radix layerwind profile depends on surface conditions such as roughness. The results arecompared against independent data collected during the Koorin field campaign. Theflux-profile relationship for wind speed is dependent on a wide-range of scales ofterrain roughness. First the ML transport coefficient for momentum flux C* D dependson small-scale roughness elements as affect the aerodynamic roughness length zo .Second, shape parameter D M depends on resolvable-scale topographic variations asaffect the standard deviation of terrain elevation Ïz . Such dependence over the widerange of scales should be expected because the radix layer profile equations weredesigned and calibrated as the average over a heterogeneous region, rather thanbeing for one column over a single land use.Sebuah persamaan baru keterkaitan antara fluks dan profil untuk angin pada kondisikonvektif dibangun dari teori transpor konvektif dan teori lapisan radix. Data darieksperimen lapangan di Minnesota digunakan untuk kalibrasi ulang. Data eksperimenlapangan BLX96 digunakan untuk menguji kebergantungan profil angin pada kondisipermukaan. Data ekperimen lapangan di Koorin digunakan untuk pembanding.Persamaan keterkaitan antara fluks dan profil untuk angin bergantung pada berbagaiskala kekasaran permukaan. Pertama, koefisien transpor untuk fluks momentumbergantung pada elemen kekasaran permukaan skala kecil. Kedua, parameter bentukprofil bergantung pada variasi berskala topografi. Kebergantung pada berbagai skalaseperti ini adalah konsekuensi logis dari persamaan profil di lapisan radix yangdidesain dan dikalibrasi menggunakan eksperimental data yang mengakomodasipengaruh berbagai skala.